THERAPEUTIC ACTIVITIES OF GARLIC CONSTITUENT PHYTOCHEMICALS - Ashfaq, F; Ali, Q; Haider, MA; Hafeez, MM; Malik, A (Biological and Clinical Sciences Research Journal, 2021)
Garlic (Allium sativum L.) has medicinal value but also an important dietary component for centuries. It belongs to the family of Liliaceae, which is mostly grown and found in Ethiopia and Africa. Ethiopian garlic has been mostly used in traditional medicines. Inhibitory activity of garlic extract has been reported by various researchers for Lactobacillus acidophilus, Staphyloccocus aureus, Nocardia asteroids, pseudomonas aeruginosa, actinomyces viscosus, veillonella alcaligens bacterial strains. The garlic paste and lime was used for mouth sore, sore throat and also can be used in toothpaste to prevent dental caries. The present review describes the potential of garlic phytochemicals for the improvement of the immune system against diseases in humans.